Length-weight relationships and condition factors of the whitespotted grouper Epinephelus coeruleopunctatus in the coastal waters of Padang City, Indonesia - Usman Bulanin; Masrizal Masrizal; Zainal A. Muchlisin (Syiah Kuala University, 2017)
The whitespotted grouper Epinephelus coeruleopunctatus is one of the commercial marine fish species occurred in the coastal waters of Padang city, Indonesia. The population of the whitespotted grouper has been declining over last decade. Unfortunately, there was a lack of information on the biology of this species was available. Hence, the objectives of the study were to examine the length-weight relationships and condition factors of the whitespotted grouper harvested from coastal waters of Padang city, Indonesia. The fish sampling was carried out from April to October 2013. The fish samples were weighed for total body weight and measured for total length. The result showed that the male grouper has W = (3.1538 10 –5) L 2.8613, while the female has W= (3.8617 10–5) L 2.8384. Both sexes male and female displayed the negative growth pattern.